Genome‐wide DNA methylation profiling of gastric cardia cancer. Issue 2 (29th November 2022) - Lin, Runhua; Qian, Yanli; Zhang, Jinhai; Xia, Di; Guo, Dongming; Hong, Liangli; Qing, Bojuan; Xu, Muming; Huang, Yiteng; Lin, Wenting; Chen, Guangcan; Liu, Shuhui
Abstract: Background and Aim: Aberrant DNA methylation has been found in various cancer types including gastric cancer, yet the genome‐wide DNA methylation profile of gastric cardia cancer (GCC) remains unclear. Therefore, we aimed to profile the DNA methylation pattern of GCC and identify promising diagnostic epigenetic biomarkers. Methods: We investigated the genome‐wide DNA methylation pattern in eight pairs of GCC and adjacent normal tissues using Illumina 850K microarrays. Subsequently, bisulfite‐pyrosequencing and quantitative real‐time PCR were performed on eight pairs of GCC‐adjacent normal tissues for validation. Finally, we performed immunohistochemistry to examine ADHFE1 expression on 126 pairs of GCC‐adjacent normal samples. Results: DNA methylome analysis showed global hypomethylation and local hypermethylation of promoter cytosine‐phosphate‐guanine (CpG) islands (CGIs) in GCC tissues compared with gastric cardia normal mucosa ( P < 2.2 × 10 −16 ). Differential methylation analysis identified a total of 91 723 differentially‐methylated probes (DMPs), and the candidate gene with the largest average DNA methylation difference mapped to ADHFE1 (mean Δ β = 0.53). Subsequently, three DMPs in the ADHFE1 promoter were validated by pyrosequencing. Notably, the mean methylation level of the three candidate DMPs ( ADHFE1 _cg08090772, ADHFE1 _cg19283840, and ADHFE1 _cg20295442) was negatively associated with ADHFE1 mRNA expression level (Spearman rho = −0.64, P = 0.01). Moreover, both mRNA ( P = 0.0213) and protein ( P < 0.0001) expression of ADHFE1 were significantly decreased in GCCs compared with the adjacent normal tissues. Conclusions: Our results reveal DNA methylation aberrations in GCC and that ADHFE1 gene DNA methylation contributes to the risk of GCC, thus providing novel mechanistic insights into gastric cardia cancer carcinogenesis. Abstract : Lin et al. perform genome‐wide DNA methylation analyses on 8 pairs of normal gastric cardia mucosa and gastric cardia cancer specimens, and identify global hypomethylation and aberrant hypermethylation in gene promoter regions in gastric cardia cancer. They find aberrant down‐regulation of ADHFE1 gene in gastric cardia cancer, which is associated with promoter hypermethylation.